2021
DOI: 10.3389/fnins.2021.726825
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variation in Sympathetic Nerve Distribution in the Human Spleen

Abstract: Introduction: The cholinergic anti-inflammatory pathway (CAIP) has been proposed as an efferent neural pathway dampening the systemic inflammatory response via the spleen. The CAIP activates the splenic neural plexus and a subsequent series of intrasplenic events, which at least require a close association between sympathetic nerves and T cells. Knowledge on this pathway has mostly been derived from rodent studies and only scarce information is available on the innervation of the human spleen. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This is important because the current model of the CAP, which was developed largely in rodent models, envisions a close association of sympathetic nerves with cholinergic T cells in the white pulp. Previous research performed with human tissue found that noradrenergic innervation of human spleen is mainly localized to the arterial vasculature and very sparse in the white pulp compared to that of rodent spleens (Cleypool et al, 2021 , Hoover et al, 2017 , Verlinden et al, 2019 ). Our findings support this view of sparse innervation of splenic parenchyma by using donor tissue immediately fixed while still viable and treated with two different antigen retrieval protocols.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is important because the current model of the CAP, which was developed largely in rodent models, envisions a close association of sympathetic nerves with cholinergic T cells in the white pulp. Previous research performed with human tissue found that noradrenergic innervation of human spleen is mainly localized to the arterial vasculature and very sparse in the white pulp compared to that of rodent spleens (Cleypool et al, 2021 , Hoover et al, 2017 , Verlinden et al, 2019 ). Our findings support this view of sparse innervation of splenic parenchyma by using donor tissue immediately fixed while still viable and treated with two different antigen retrieval protocols.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous immunohistochemical studies evaluated sympathetic innervation of human spleen, using primarily archived autopsy samples and a limited number of fresh frozen samples (Cleypool et al, 2021 , Hoover et al, 2017 , Verlinden et al, 2019 ). This work was consistent in finding that a vast majority of noradrenergic nerves in the human spleen occurred around the arterial vasculature, where they were localized to perivascular adventitia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, much of our knowledge regarding the architecture and function of the lymphatic system derives from rodents 11 , with recent studies noting a series of key architectural differences compared to humans [12][13][14] . Indeed, recent 3D imaging and topological mapping of the murine LN 15,16 have described a mesh-like network composed of fibroblastic reticular cells (FRCs) that provide the homing zone for T cells and may mediate B cell homeostasis 17 .…”
Section: Mainmentioning
confidence: 99%
“…The autonomic nervous system provides control of host immune defense mechanisms through innervation from sympathetic postganglionic neurons, specifically the splenic nerve for the SPL and anatomically paired nerve fibers for respective LNs 10 . However, much of our knowledge regarding the architecture and function of the lymphatic system derives from rodents 11 , with recent studies noting a series of key architectural differences compared to humans 1214 .…”
Section: Mainmentioning
confidence: 99%